The International Logistics Center of Turkey: Situational Analysis of Mersin Port’s Seaways Logistics - COŞKUNTUNCEL, Ahu; RAD, Sevgi TÜZÜN (International Journal of Management and Sustainability, 2015)
In these days, the convergence of economies and the extension of manufacturing and marketing to international levels increase the importance of the safely transporting of goods along with logistics and the related activities. Today, as in the world trade, an important portion of Turkey’s trade is being carried via marine transportation whose domain of activities carries international significance. Mersin Province, with its potential of logistics and the logistics services it provides, makes valuable contributions to both the international trade and the domestic market of Turkey. In this context, this study aims at examining the current situation of seaways logistics of Mersin Province, which is viewed as the largest port of Turkey and the logistics base of Mediterranean Region, as well as the fundamental problems of the sector. In this study, the research material is made up of data obtained through the face-to-face interviews with the representatives of the firms which operate in Mersin Province in the sector of international transportation. Descriptive statistical analyses have been utilized in the evaluation of the data. With this study, it has been established that the province’s geographical position is being viewed to be a great advantage, but also that the employment of unqualified work force affects the sector negatively, that there are deficiencies in the port’s infrastructure, and that the firms do not yet have institutionalized frameworks.